Effect of the somatic factor on performance in shot put in relation to the spin and classical techniques - Haleczko, A.; Korzewa, L.; Misiolek, E.; Wlodarczyk, U. (Journal of Kinesiology and Exercise Sciences, 2013)
Introduction. Changing the shot put technique by replacing the linear run-up with a rotational run-up allowed athletes to increase the distance and duration by which their strength affected the shot. Thanks to the innovation, shot put distance from a running start increased between 2.5 m and 2.7 m compared to a standing start. Currently, most athletes use new technique, although it is more difficult. Statements by various authors on somatic preferences for shot-putters in terms of both discussed techniques are often contradictory and unsupported by research. As a result, these statements can be treated merely as intuitive observations. Aim. This study was motivated by a lack of research on the greater effectiveness of the spin technique. Material and methods. Research material comprised somatic data and results of 67 shot-putters (49 using the spin technique and 18 using the classic (glide) technique) derived from the 2009 ranking list, acquired from the Internet. A lack of differences in results and morphological parameters allowed us to combine the two groups into one group. Statistical analysis was conducted using basic numerical characteristics, with correlations calculated using the Pearson and Spearman methods. To allow a more accurate comparison, 2 groups of 18 athletes somatically similar to the shot-putters using the classic technique were chosen from the group of 49. Results. Body height of the `spin` group, chosen based on their body mass, was 4.2 cm lower than in the `classic` group, meaning that, for all practical purposes, the values were equal. The former group showed statistically significant correlations, while the latter group showed no correlation between their results and either somatic trait as well as between the 2 variables. The observed correlations indicate that the athletes had a disproportionate body build. A graphical comparison of the athletes` body mass and results allowed us to divide them into the categories of lightweight (up to 114 kg) and heavyweight (above 114 kg). Lightweight shot-putters showed a negative (r = -0.23) correlation with their results, while heavyweight shot-putters showed a positive correlation (r = 0.40). The aforementioned relationships in a reference group of decathletes showed progression up to about 90 kg of body mass and above 90 kg showed regression, similar to the case of lightweight shot-putters. A positive correlation in the heavyweight group (above 114 kg) was inconsistent with the opinion of Forbes, who estimated the upper limit of LMB at 100 kg, and motivated us to elaborate on this phenomenon. Conclusions. In summary, we emphasize the role of somatomotor measurements in assessing the level of training in athletes, noting at the same time that these measurements cannot be construed as to indicate illegal doping.